Fabrication and characterization of strontium-doped hydroxypatite bioceramics scaffolds for bone implant application: a preliminary study - Che Murad, Mardziah; Iis, Sopyan; Mohd, Reusmaazran; Che Hak, Rohaida; Zakaria, Ahmad; Mohd, Reusmaazran (Trans Tech Publications, Switzerland, 2010)
In this study, strontium doped hydroxyapatite (SrHA) nanopowder was synthesized through a sol-gel method. Strontium concentration was varied from 0 to 15 mol%. The obtained gel was then dried and subsequently subjected to 900 ºC calcination. SrHA porous bodies were fabricated by using polymeric sponge method with different chemical compositions (0, 2 and 10 mol% SrHA). To prepare the porous samples, the synthesized SrHA powders was mixed with distilled water and appropriate amount of dispersing agent followed by drying in the ambient air for 72 hours. The dried impregnated sponges were then sintered at 1300°C for 3 hours. The XRD patterns showed high crystallinity of HA phase only for all porous samples. Morphological evaluation by FESEM measurement revealed that the SrHA scaffolds were characterized by a uniform distribution of interconnected pores (200-800 µm). Compression test on the porous scaffolds revealed that doping 10 mol% of strontium in HA has increased the compressive strength compared to the undoped HA